2016
DOI: 10.1128/aem.00271-16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Shiga Toxin-Producing Escherichia coli and Enteropathogenic E. coli Strains Isolated from French Coastal Environments

Abstract: Shiga toxin-producing Escherichia coli (STEC) and enteropathogenic E. coli (EPEC) strains may be responsible for food-borne infections in humans. Twenty-eight STEC and 75 EPEC strains previously isolated from French shellfish-harvesting areas and their watersheds and belonging to 68 distinguishable serotypes were characterized in this study. High-throughput real-time PCR was used to search for the presence of 75 E. coli virulence-associated gene targets, and genes encoding Shiga toxin (stx) and intimin (eae) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
4
24
0
4
Order By: Relevance
“…In accordance with previous studies, the positive association between paa and diarrhea was also observed in our study. Balière et al (2016) observed a significantly higher (60%) occurrence of paa in EPEC isolates from environment samples, which is similar to the frequency we observed in raw meat isolates (63.6%) in this study. paa was much more frequently detected in strains isolated from raw meats than from other sources, and was especially higher than strains from healthy carriers (14.8%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with previous studies, the positive association between paa and diarrhea was also observed in our study. Balière et al (2016) observed a significantly higher (60%) occurrence of paa in EPEC isolates from environment samples, which is similar to the frequency we observed in raw meat isolates (63.6%) in this study. paa was much more frequently detected in strains isolated from raw meats than from other sources, and was especially higher than strains from healthy carriers (14.8%).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have investigated the presence of AT genes in EPEC (Abreu et al, 2013; Balière et al, 2016). In the present study, four AT genes ( ehaC, espP, pet , and pic ) were detected.…”
Section: Discussionmentioning
confidence: 99%
“…All shellfish-harvesting farms are classified as Class A, B or C and this is defined by the E. coli concentrations in the harvested bivalves (Table 1). The sanitary classification of shellfish-harvesting areas in Europe is an important measure that helps to prevent shellfish food-borne outbreaks (Baliere et al, 2016). Table 1.…”
Section: Food Safety Aspects Of Bivalvesmentioning
confidence: 99%
“…Shiga genes are encoded in stx phages. There are many other genes associated with STEC virulence, such as saa, paa, ehaA, iha, sab and more (Baliere et al, 2016), but these are not further discussed here. Two main Shiga toxins have been described:…”
Section: Virulence Genesmentioning
confidence: 99%
See 1 more Smart Citation